Nilai-Nilai Pendidikan Akhlak Bagi Anak Dalam Film Kartun Animasi Omar dan Hana - Ana Adilla; Al Ikhlas (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to analyze the values of moral education for children contained in the animated cartoon films of Omar and Hana episodes of “Makan Besar” and “Kasihan Penyu”. The type of research used is library research. The value of moral education contained in the episode is the value of moral education to Allah SWT, for example: being grateful, sincere, and obeying Allah SWT. Morals towards the family for example respecting parents and being devoted to parents. Morals towards the community for example: sharing with other neighbors, helping each other, giving charity. Morals towards the environment: keeping clean and loving animals. The result of this study is expected to be a lesson or benchmark for children and parents to be able to provide good viewing media for their children.